Bound by Our Constitution : Women, Workers, and the Minimum Wage. - Hart, Vivien (Princeton University Press, 2001)
What difference does a written constitution make to public policy? How have women workers fared in a nation bound by constitutional principles, compared with those not covered by formal, written guarantees of fair procedure or equitable outcome? To investigate these questions, Vivien Hart traces the evolution of minimum wage policies in the United States and Britain from their common origins in women's politics around 1900 to their divergent outcomes in our day. She argues, contrary to common wisdom, that the advantage has been with the American constitutional system rather than the British. Ba.